Role of the Europe–China Pattern Teleconnection in the Interdecadal Autumn Dry–Wet Fluctuations in Central China - Linwei Jiang; Wenhao Gao; Kexu Zhu; Jianqiu Zheng; Baohua Ren (Atmosphere, 2024)
Based on statistical analyses of long-term reanalysis data, we have investigated the interdecadal variations of autumn precipitation in central China (APC-d) and the associated atmospheric teleconnection. It reveals that the increased autumn rainfall in central China during the last decade is a portion of the APC-d, which exhibits a high correlation coefficient of 0.7 with the interdecadal variations of the Europe–China pattern (EC-d pattern) teleconnection. The EC-d pattern teleconnection presents in a “+-+” structure over Eurasia, putting central China into the periphery of a quasi-barotropic anticyclonic high-pressure anomaly. Driven by positive vorticity advection and the inflow of warmer and moist air from the south, central China experiences enhanced ascending motion and abundant water vapor supply, resulting in increased rainfall. Further analysis suggests that the EC-d pattern originates from the exit of the North Atlantic jet and propagates eastward. It is captured by the Asian westerly jet stream and proceeds towards East Asia through the wave–mean flow interaction. The wave train acquires effective potential energy from the mean flow by the baroclinic energy conversion and simultaneously obtains kinetic energy from the basic westerly jet zones across the North Atlantic and the East Asian coasts. The interdecadal variation of the mid-latitude North Atlantic sea surface temperature (MAT-d) exhibits a significant negative relationship with EC-d, serving as a modulating factor for the EC-d pattern teleconnection. Experiments with CMIP6 models predict that the interdecadal variations in APC-d, EC-d, and MAT-d will maintain stable high correlations for the rest of the 21st century. These findings may contribute to forecasting the interdecadal autumn dry–wet conditions in central China.